2021
DOI: 10.4103/jfmpc.jfmpc_2526_20
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a “convergent” framework of action against childhood malnutrition in urban informal settlements of Mumbai

Abstract: Context: The National Nutrition Mission (POSHAN Abhiyaan) intends to “converge” nutrition-related program components across sectors (nutrition, health, water, and sanitation). In this study, we have examined the perspectives of Anganwadi workers (AWWs), the frontline workers of the Integrated Child Development Services, on working in convergence with the public health sector. Methods: This exploratory qualitative study was done between June 2018 and June 2019 in two urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Over the years SNEHA has built strong partnerships with public systems such as the Integrated Child Development Services (ICDS) and Municipal Corporation of Greater Mumbai. However, there are real-world challenges in operationalizing cross-sector convergence which could have implications for the provision of primary health care (30). An indepth study on perspectives and experiences of this collaboration indicated that effort goes into establishing and sustaining personal relationships with staff working in the public system, building trust, training their staff from time to time, disseminating information on public sector schemes, support in conducting routine activities including community mobilization, referrals, data collection and sharing which helps in improving service provision and connecting the services to the community members (31).…”
Section: Provision Of High-quality Primary Health Care Services ( C)mentioning
confidence: 99%
“…Over the years SNEHA has built strong partnerships with public systems such as the Integrated Child Development Services (ICDS) and Municipal Corporation of Greater Mumbai. However, there are real-world challenges in operationalizing cross-sector convergence which could have implications for the provision of primary health care (30). An indepth study on perspectives and experiences of this collaboration indicated that effort goes into establishing and sustaining personal relationships with staff working in the public system, building trust, training their staff from time to time, disseminating information on public sector schemes, support in conducting routine activities including community mobilization, referrals, data collection and sharing which helps in improving service provision and connecting the services to the community members (31).…”
Section: Provision Of High-quality Primary Health Care Services ( C)mentioning
confidence: 99%